Exploring The Garden as an “Interstitial Space” For Women in Francis Hodgson Burnett’s The Secret Garden and Shahrnush Parsipur’s Women Without Men - Onur Ekler (Journal of Literature and Humanities, 2025)
This article is an inquiry dedicated to exploring the function of the garden as an interstitial space for the anti-Oedipal female characters in Francis Hodgson Burnett’s famous novel, The Secret Garden (1911), Shahrnush Parsipur’s Women Without Men (1989). This inquiry is grounded on two complementary levels. As it examines the female characters’ constant exposure to systematic victimization in the restricting frames of the patriarchal dominions of Victorian England and the Iranian Regime, it also sheds light on both Burnett and Parsipur’s intentional design of the garden as a liminal zone at the nexus where magic and real converge. This article highlights the intersecting points concerning woman’s position and garden in both works though not using a direct comparative method. To show the universality of the problems concerning subjugated women in patriarchal societies, this article intentionally takes on two works across borders, having different socio-historical contexts. The originality of this article lies in the exploration regarding how both works map out the garden as a female space in contrast to the traditional view of the garden as a place that has served man’s pleasures.